Workshop on the Transformation of School Principals as Innovative and Dedicated Learning Leaders with the TPjBL Model at the SMA/SMK Forum in East Manggarai Regency - Habur, Agustinus Manfred; Payong, Marselus Ruben; Tapung, Marianus Mantovanny (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
In the face of the rapid development of technology and the increasing demand for efficient energy management, controlling household lights remotely has become an essential feature of modern smart homes. This research aims to develop and test a remote lighting control system using the Internet of Things (IoT) technology, based on Arduino, which can be operated via a smartphone application to improve energy efficiency. The method used is an experimental approach with a quantitative design, where the system's functionality is evaluated in real-life settings. The system was tested across different locations, and the results show that it functions well with response times ranging from 1.6 to 3.99 seconds, demonstrating the system's dynamic responsiveness. The system allows users to operate lights remotely, helping reduce energy consumption in households. The implications of this study suggest that the IoT-based lighting control system can significantly contribute to energy savings, increase user convenience, and reduce carbon emissions. The findings also open up possibilities for expanding smart home technologies in resource-constrained environments. Further research is recommended to test the scalability of the system in larger residential settings and to explore its integration with other smart home devices for more comprehensive energy management solutions.